Active fault diagnosis for uncertain systems using optimal test designs and detection through classification. (October 2019) - Palmer, Kyle A.; Bollas, George M.
Abstract: Fault detection and isolation (FDI) is becoming increasingly difficult due to the complexity and uncertainty of modern systems. For industrial systems with explicit models available, model-based active FDI tests can improve the capability for fault diagnosis. These tests should be determined and evaluated prior to implementation to minimize on-site computational costs. In this paper, a methodology is presented for the design optimization and assessment of tests for active fault diagnosis. The objective is to maximize the information from system outputs with respect to faults while minimizing the correlation between faults and uncertainty. After a test is designed, it is deployed with a k -nearest neighbor algorithm combined with principal component analysis.Two case studies are used to verify the proposed methodology, a three-tank system and a diesel engine. Highlights: FDI tests optimized for the quality of information extracted from uncertain systems. Ds-Optimal tests improve sensitivity and robustness in fault diagnosis. Low computational cost of detection using PCA and k-NN algorithm. Faults in a three-tank system and a diesel engine examined as case studies. Case studies show rate of correct classifications increased after test optimization.